The α(1B)-adrenoceptor subtype mediates adrenergic vasoconstriction in mouse retinal arterioles with damaged endothelium - Böhmer, Tobias (Blackwell Publishing Ltd, 2014)
BACKGROUND AND PURPOSE: The α(1)-adrenoceptor family plays a critical role in regulating ocular perfusion by mediating responses to catecholamines. The purpose of the present study was to determine the contribution of individual α(1)-adrenoceptor subtypes to adrenergic vasoconstriction of retinal arterioles using gene-targeted mice deficient in one of the three adrenoceptor subtypes (α(1)(A)-AR(−/−), α(1)(B)-AR(−/−) and α(1)(D)-AR(−/−) respectively). EXPERIMENTAL APPROACH: Using real-time PCR, mRNA expression for individual α(1)-adrenoceptor subtypes was determined in murine retinal arterioles. To assess the functional relevance of the three α(1)-adrenoceptor subtypes for mediating vascular responses, retinal vascular preparations from wild-type mice and mice deficient in individual α(1)-adrenoceptor subtypes were studied in vitro using video microscopy. KEY RESULTS: Retinal arterioles expressed mRNA for all three α(1)-adrenoceptor subtypes. In functional studies, arterioles from wild-type mice with intact endothelium responded only negligibly to the α(1)-adrenoceptor agonist phenylephrine. In endothelium-damaged arterioles from wild-type mice, phenylephrine evoked concentration-dependent constriction that was attenuated by the α(1)-adrenoceptor blocker prazosin. Strikingly, phenylephrine only minimally constricted endothelium-damaged retinal arterioles from α(1)(B)-AR(−/−) mice, whereas arterioles from α(1)(A)-AR(−/−) and α(1)(D)-AR(−/−) mice constricted similarly to arterioles from wild-type mice. Constriction to U46619 was similar in endothelium-damaged retinal arterioles from all four mouse genotypes. CONCLUSIONS AND IMPLICATIONS: The present study is the first to demonstrate that α(1)-adrenoceptor-mediated vasoconstriction in murine retinal arterioles is buffered by the endothelium. When the endothelium is damaged, a vasoconstricting role of the α(1)(B)-adrenoceptor subtype is unveiled. Hence, the α(1)(B)-adrenoceptor may represent a target to selectively modulate retinal blood flow in ocular diseases associated with endothelial dysfunction.